PENDIDIKAN SEKS BAGI ANAK USIA DINI MENURUT HADIST NABI - Nurhasanah Bakhtiar; Nurhayati (UIR PRESS, 2020)
Early age (0-6 years) is the golden age. This period is the formation period that determines adolescence and adulthood. Islam as a perfect religion has governed all lines, one of which is about educating young children, especially related to sex education. This study aims to explore how sex education for early childhood in the explanation of the Prophet's hadith. This type of research used by researchers is library research (library research) by tracing various hadith books and the work of scholars and experts related to early childhood sex education. As a qualitative study, the data analysis is used in three stages (data reduction, data display, and concluding). The results of this study state that sex education for young children does not explain sex itself to children, but means: first, explain and introduce their identity as men or women through differences in genitalia. Second, it teaches children moral values ​​and character and politeness of decency. Third, provide a warning for parents to educate their children at an early age following the religious directions contained in the Koran and Hadith.